2020
DOI: 10.3389/fsufs.2020.607343
|View full text |Cite
|
Sign up to set email alerts
|

What Did We Learn From Plant Growth-Promoting Rhizobacteria (PGPR)-Grass Associations Studies Through Proteomic and Metabolomic Approaches?

Abstract: Plant growth stimulation by microorganisms that interact in a mutually beneficial manner remains poorly understood. Understanding the nature of plant-bacteria interactions may open new routes for plant productivity enhancement, especially cereal crops consumed by humans. Proteomic and metabolomic analyses are particularly useful for elucidating these mechanisms. A complete depiction of these mechanisms will prompt researchers to develop more efficient plant-bacteria associations. The success of microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 154 publications
0
16
0
1
Order By: Relevance
“…The promotion of root and shoot growth is one of the main effects of PGPR on plants. Various studies report increases in plant total biomass from 20 to 60% after PGPR application [106,107]. However, this effect was not observed in some recent studies on PGPR-enhanced phytoextractions with Brassica species [98,100,104,105].…”
Section: The Use Of Pgprmentioning
confidence: 93%
“…The promotion of root and shoot growth is one of the main effects of PGPR on plants. Various studies report increases in plant total biomass from 20 to 60% after PGPR application [106,107]. However, this effect was not observed in some recent studies on PGPR-enhanced phytoextractions with Brassica species [98,100,104,105].…”
Section: The Use Of Pgprmentioning
confidence: 93%
“…Moreover, a very high Na + ion concentration in plant cells results in various physiological disorders, such as reduced flowering or fruiting [13]. The following metabolic processes are very sensitive to increased salinity: transport of electrons, phosphorylation, photosynthesis and photorespiration [48,66]. Salt stress significantly lowers the efficiency of photosynthesis due to its multi-level action.…”
Section: Salinizationmentioning
confidence: 99%
“…Land, as mentioned above, also loses its buffer and antipollution properties [ 56 ]. The long-term salinization process, without any human intervention, results in a drastic decrease in soil fertility, and thus its uselessness [ 66 ]. Increased salt levels not only damage soil structure and microbial activity, but they also limit plant development by generating osmotic impact, hazardous ion and mineral imbalances, or metabolic diseases [ 51 , 67 ].…”
Section: Climate Change and Its Impact On Agriculturementioning
confidence: 99%
“…Whereas oxidative burst during plant-pathogen interactions has been extensively described, studies concerning the modulation of redox activities in plants interacting with beneficial microbes remain sparse. However, modulation of antioxidant enzyme activities has been observed during some interactions between plants and plant growth-promoting rhizobacteria (PGPR) [15,16]. Analysis of sugarcane root transcriptome showed that many genes involved in the redox process were upregulated and that peroxidase and catalase enzyme activities were also significantly upregulated in response to the Burkholderia anthina MYSP113 [16].…”
Section: Introductionmentioning
confidence: 99%